2021
DOI: 10.1002/col.22744
|View full text |Cite
|
Sign up to set email alerts
|

Color appearance of color chips under light‐emitting diode lamps

Abstract: Many kinds of research have been undertaken on color constancy under various illuminations; however, not many people have studied this domain in the context of vivid colored light. In this article, 23 color chips were assessed using the elementary color‐naming method under 13 RGB‐LED illuminations of six hues as red, yellow, green, cyan, blue, and magenta. A total of 100 subjects participated in the study and reported that color chips of cyan, yellow, and green light were not good as compared to the others. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the previous report, 1 we found that the area perception between less vivid light conditions and the D65 light as the reference had a small difference that was shown by a high area ratio index, which ranged from 0 to 1 as no area perception compared to the reference area and having the exact amount of area perception same as the reference area, respectively. We also presented the perception color constancy index calculated based on the perceptual color space determined by the distance between the perception adapted to the illumination distance and the perception without adapting to the illumination distance.…”
Section: Methodsmentioning
confidence: 66%
See 4 more Smart Citations
“…In the previous report, 1 we found that the area perception between less vivid light conditions and the D65 light as the reference had a small difference that was shown by a high area ratio index, which ranged from 0 to 1 as no area perception compared to the reference area and having the exact amount of area perception same as the reference area, respectively. We also presented the perception color constancy index calculated based on the perceptual color space determined by the distance between the perception adapted to the illumination distance and the perception without adapting to the illumination distance.…”
Section: Methodsmentioning
confidence: 66%
“…Experimental booths: the left (A) shows the booth used in Experiment 1. The right (B) shows an example of the apparatus for Experiment 2, in which the booth was separated into the test room illuminated by various colored lights and the subject room illuminated by only white light 1 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations